2020
DOI: 10.1186/s12889-020-8295-7
|View full text |Cite
|
Sign up to set email alerts
|

Dieting, body weight concerns and health: trends and associations in Swedish schoolchildren

Abstract: Background: Dieting is a risk factor of both eating disorders and obesity. The aim was to examine time trends of dieting in Swedish adolescents, and explore how dieting and body weight dissatisfaction are related to selfreported health, wellbeing and health behaviours. Methods: Analyses of cross-sectional Swedish data from HBSC (Health Behaviour in School-aged Children) surveys 1994-2014. In total, about 30,000 girls and boys in the age of 11, 13 and 15 years participated. Data was collected by using classroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 43 publications
1
9
0
1
Order By: Relevance
“…Concerns about nutrition issues in adolescents are growing [ 16 , 17 ]. The eating habits and nutritional knowledge acquired during this stage are key factors for the creation of good eating habits in adulthood [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concerns about nutrition issues in adolescents are growing [ 16 , 17 ]. The eating habits and nutritional knowledge acquired during this stage are key factors for the creation of good eating habits in adulthood [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We defined screen time as including watching TV, videos, or DVDs; playing games on a computer or game console; and using a computer for email, the internet, or homework ( 40 , 47 ). For analysis, we dichotomized the variable; the cutoff point was 4 h or more on weekdays ( 49 ).…”
Section: Methodsmentioning
confidence: 99%
“…In line with the aforementioned statements, studies showed that teenagers misperceive their weight, considering their size heavier than it really is (overestimation), or smaller than it actually is (underestimation) [ 16 ]. Factors associated to misperception such as gender, diet, and maternal attitude were reported [ 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, body image is associated with higher rates of body dissatisfaction [ 34 ]. This issue is related to children’s seeking an ideal body type established by society [ 21 , 35 ]. Body image has gender characteristics: for girls, body satisfaction is related to weight, facial features, and skin appearance [ 36 ], while for boys, it is represented by strength, muscle mass development, and speed [ 37 ].…”
Section: Introductionmentioning
confidence: 99%